1994
DOI: 10.1093/carcin/15.12.2769
|View full text |Cite
|
Sign up to set email alerts
|

Loss of heterozygosity of the human cytosolic glutathione peroxidase I gene in lung cancer

Abstract: The consistent deletion of 3p21 in lung cancer has led to intensive efforts to identify a lung tumor suppressor gene at this locus. We recently mapped the gene for the selenium-dependent drug-detoxifying enzyme glutathione peroxidase 1 (GPX1) to this location by in situ hybridization. We developed a polymerase chain reaction-based assay which demonstrated the existence of three GPX1 alleles characterized by the number of alanines in a polyalanine coding sequence in exon 1. These three alleles produced a hetero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(58 citation statements)
references
References 28 publications
3
55
0
Order By: Relevance
“…Besides the difference in the length of the polyalanine track the Ala6 allele is in complete linkage disequilibrium with an amino acid substitution (Leu198Pro) in the coding region and two more base substitutions outside the coding regions. 8 Thus, this allele is the most likely to code for a functionally different protein.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides the difference in the length of the polyalanine track the Ala6 allele is in complete linkage disequilibrium with an amino acid substitution (Leu198Pro) in the coding region and two more base substitutions outside the coding regions. 8 Thus, this allele is the most likely to code for a functionally different protein.…”
Section: Resultsmentioning
confidence: 99%
“…7 Therefore it is plausible that a genetic alteration or polymorphisms in the GPX1 gene may also have an effect on prostate cancer risk. The presence of a GCG repeat polymorphism coding for alanine residues in a polyalanine tract of GPX1 was described by Moscow et al 8 They have also reported that other polymorphisms co-segregate with one of the alleles, a proline to leucine substitution at codon 198, a T to C substitution at ĂŸ 2 and a G for A substitution at 7 592. In a recent study it was shown that the Pro198Leu polymorphism was significantly associated with the risk of developing lung cancer in a case -control study confirming the role of GPX1 as a potent risk factor in tumour development.…”
Section: Introductionmentioning
confidence: 82%
“…Perhaps the best candidate is GPx-1, because an association with polymorphisms and the risk of lung cancer has been reported, as has loss of heterozygosity at this locus in several cancer types (9)(10)(11)(12). In fact, an association between a polyalanine polymorphism in exon 1 and the risk of young-onset prostate cancer has been reported (28).…”
Section: Discussionmentioning
confidence: 99%
“…A functional difference in GPx-1 genotype at codon 198 was demonstrated by exclusively expressing each allele in breast cancer cells and showing that the leucinecontaining allele is less responsive to selenium supplementation than the proline allele, suggesting a possible functional consequence for the allelic identity at the codon 198 (148). Furthermore, an additional common polymorphism exists in which a variable number of tandem alanine codons, 4, 5, or 6 repeats, are found in GPx1 exon 1 (235). A case-control study found an increased frequency of the polyalanine repeats in the prostate cancer cases compared with controls; however, the study found no significant association between Gpx1 genotype and the risk for prostate cancer (181).…”
Section: From Selenium To Selenoproteins 789mentioning
confidence: 92%